Triple-P Panel (Procalcitonin, Presepsin and Pentraxin3) to Confirm Sepsis - Kadim, Muayad Mahdi; Al-Dahmoshi, Hussein O.M. (Iraqi Journal of Science, 2024)
A total of 65 blood samples (25 culture positive sepsis and 40 culture negative sepsis) from patients with sepsis symptoms who resided in the ICU of Hilla city hospitals, were collected, as well as 25 samples as a control (healthy persons) during a period from January to June 2022. Data was documented at the time of admission to the ICU. Regarding PSN and PCT concentration (P value= 0.001), the control group had a significant difference from both the two patients’ groups (culture positive and negative groups of sepsis). Whereas the difference was not significant for the PTX3 concentration among patients and control (P value = 0.56). Furthermore, PSN and PCT concentrations did not significantly differ between the culture positive and culture negative groups of sepsis (P value > 0.05). Moreover, there was a significant strong positive correlation between PSN and PCT (r = 0.500; P <0.001).